2017
DOI: 10.1200/jop.2016.014431
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Drugs: An International Comparison of Postlicensing Price Inflation

Abstract: Cancer drug prices are rising substantially, both at their initial marketing price and, in the United States, at postlicensing prices. In the United Kingdom, the Pharmaceutical Price Regulation Scheme, an agreement between the government and the pharmaceutical industry, controls health care costs while allowing a return on investment and funds for research. The increasing costs of cancer drugs are approaching the limits of sustainability, and a similar government-industry agreement may allow stability for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 9 publications
1
34
0
2
Order By: Relevance
“…An analysis of the top 10 selling cancer medicines in the United States and the United Kingdom found that US launch prices were 42% higher than in the United Kingdom . By 2015, their average annual price inflation was 8.8% in the United States but was restricted by price regulations to 0.33% in the United Kingdom.…”
Section: Spiraling Cancer Medicine Pricesmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the top 10 selling cancer medicines in the United States and the United Kingdom found that US launch prices were 42% higher than in the United Kingdom . By 2015, their average annual price inflation was 8.8% in the United States but was restricted by price regulations to 0.33% in the United Kingdom.…”
Section: Spiraling Cancer Medicine Pricesmentioning
confidence: 99%
“…24 An analysis of the top 10 selling cancer medicines in the United States and the United Kingdom found that US launch prices were 42% higher than in the United Kingdom. 25 By 2015, their average annual price inflation was 8.8% in the United States but was restricted by price regulations to 0.33% in the United Kingdom. During 2005 through 2017 (mean, 8-year follow-up) in the United States, the mean cumulative cost increase (adjusted for general inflation) for 24 injectable cancer drugs was 19.1% (95% CI, 11%-27.2%).…”
Section: Spiraling Cancer Medicine Pricesmentioning
confidence: 99%
“…That annual price increases of more than 5%‐10% (adjusted for inflation) be justified by additional research discoveries or benefits after the drug launch is already standard practice in other countries, but not in the U.S …”
Section: Proposed Effective Solutionsmentioning
confidence: 99%
“…The devolution of research responsibilities to contract research organizations (CROs) has increased bureaucracy without clearly improving patient safety or the quality of trial conduct and clinical research. There also is growing concern regarding the exorbitant prices of new cancer drugs, as well as the unrelenting annual price increases of 10% to 20% among older agents, even in cases in which the drug is off‐patent . This results in a diminishing percentage of patients able to access affordable therapies.…”
Section: Introductionmentioning
confidence: 99%
“…There also is growing concern regarding the exorbitant prices of new cancer drugs, as well as the unrelenting annual price increases of 10% to 20% among older agents, even in cases in which the drug is off-patent. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] This results in a diminishing percentage of patients able to access affordable therapies.…”
Section: Introductionmentioning
confidence: 99%